Estudo das propriedades e desempenho mecânico de juntas soldadas por fricção pontual de poli (metacrilato de metila) (PMMA) - Oliveira, Pedro Henrique Freiria de (2012)
Polymeric components have been replacing traditional materials such as glass or metals in a wide range of applications due to their advantages, such as optimized specific strength (weight-to-strength ratio), reduced fabrication time and costs, and design flexibility. The increasing use of polymeric materials in engineering requires efficient and environmental friendly fabrication and processing technologies. Initially developed for metals, the Friction Stir Spot Welding (FSSW) is a joining technique with short process cycles, low energy consumption and no need of consumables. Friction Stir Spot Welding has excellent performance in welding of lightweight alloys, showing promising results in thermoplastic welding. This study investigates the relationships between friction stir spot welding parameters (tool rotational speed, plunge rate and dwell time) and weld properties (joint geometry, process temperature, microstructure, lap shear resistance and failure mechanisms) in polymethylmethacrylate (also known as PMMA) single-spot joints. PMMA friction stir spot welds showed similar mechanical performance in comparison to other current welding techniques, with equal or shorter welding cycle times. Differential scanning calorimetry and gel permeation chromatography analysis demonstrated that polymer degradation level in the weld region was negligible. The statistical models proposed for FSSW of PMMA showed good repeatability and reproducibility for the investigated material and welding ranges. Moreover, the feasibility of the Friction Spot Welding (FSpW) a new joining technology developed as a further improvement of the friction stir spot welding was successfully demonstrated in thermoplastic polymers for the first time worldwide. Sound FSpW-single lap joints on PMMA were produced and their properties studied within an exploratory study.